2014
DOI: 10.1371/journal.pone.0097851
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Transmembrane Prostatic Acid Phosphatase Display Increased GABAergic Transmission and Neurological Alterations

Abstract: Prostatic acid phosphatase (PAP), the first diagnostic marker and present therapeutic target for prostate cancer, modulates nociception at the dorsal root ganglia (DRG), but its function in the central nervous system has remained unknown. We studied expression and function of TMPAP (the transmembrane isoform of PAP) in the brain by utilizing mice deficient in TMPAP (PAP−/− mice). Here we report that TMPAP is expressed in a subpopulation of cerebral GABAergic neurons, and mice deficient in TMPAP show multiple b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The GABAergic abnormalities observed here likely contribute to the pattern of behavioural differences. For example, it is well-established that striatal GABAergic neurotransmission is involved in PPI 81 , 82 and anxiety-like behaviour. 82 …”
Section: Discussionmentioning
confidence: 99%
“…The GABAergic abnormalities observed here likely contribute to the pattern of behavioural differences. For example, it is well-established that striatal GABAergic neurotransmission is involved in PPI 81 , 82 and anxiety-like behaviour. 82 …”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of PAP in prostate cancer tissue has been shown to be reduced . The studies carried out in our PAP‐knockout mouse model showed that a deficiency in the expression of PAP leads to the development of prostate adenocarcinoma , increased acinar cell proliferation in the submandibular salivary glands (SMGs) and disturbed neurotransmitter signaling in the brain . The common characteristic amongst these organs is that the epithelial cells as well as neurons are polar secretory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies demonstrate ACPP is expressed in the brain and suggest that PAP plays a critical role in preventing cell proliferation, cancer cell invasion, and neurite retraction [ 11 , 12 ]. PAP’s function has critical implications in mental health diseases such as anxiety, depression, and schizophrenia [ 5 ], neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease [ 13 ], and possibly in brain cancer. Yet, little is known about ACPP’s function and regulation in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, ACPP is expressed in brain regions related to language, motor coordination, cognitive function, and self-awareness [ 4 7 ], suggesting it plays an important role in brain health. While PAP’s role within nervous tissue is not fully elucidated, it is known to localize in synaptic nerve endings [ 5 ] and co-localizes with SNAPIN [ 14 ], a protein that binds to SNAP-25 [ 15 ], which is associated with schizophrenia [ 16 19 ]. Recent studies further suggest PAP is a key cell growth regulator and potential tumor suppressor gene in the prostate [ 8 10 ], but PAP may have similar roles in the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation